Indirect effects of habitat loss via habitat fragmentation: A cross-taxa analysis of forest-dependent species. (January 2020) - Püttker, Thomas; Crouzeilles, Renato; Almeida-Gomes, Mauricio; Schmoeller, Marina; Maurenza, Daniel; Alves-Pinto, Helena; Pardini, Renata; Vieira, Marcus V.; Banks-Leite, Cristina; Fonseca, Carlos R.; Metzger, Jean Paul; Accacio, Gustavo M.; et al.
Abstract: Recent studies suggest that habitat amount is the main determinant of species richness, whereas habitat fragmentation has weak and mostly positive effects. Here, we challenge these ideas using a multi-taxa database including 2230 estimates of forest-dependent species richness from 1097 sampling sites across the Brazilian Atlantic Forest biodiversity hotspot. We used a structural equation modeling approach, accounting not only for direct effects of habitat loss, but also for its indirect effects (via habitat fragmentation), on the richness of forest-dependent species. We reveal that in addition to the effects of habitat loss, habitat fragmentation has negative impacts on animal species richness at intermediate (30–60%) levels of habitat amount, and on richness of plants at high (>60%) levels of habitat amount, both of which are mediated by edge effects. Based on these results, we argue that dismissing habitat fragmentation as a powerful force driving species extinction in tropical forest landscapes is premature and unsafe. Highlights: Habitat loss has indirect effects on species richness through habitat fragmentation. Direct effects of habitat fragmentation on species diversity are negative. Effects of habitat amount and fragmentation vary across habitat amount levels. Fragmentation effects are induced mainly by edge effects. We call for caution to dismiss fragmentation as a driver of species extinction.